Performance Measurement of Regional Financial Management of East Java Province - Priyono, Joko (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Purpose: This study aims to measure the financial performance of the East Java Province in 2022-2024. Methodology/Approach: The research method used is descriptive statistical analysis. The measuring instruments used in this analysis are independence ratio, effectiveness ratio, efficiency ratio, activity ratio, and growth ratio. The analysis in this study is the processing of data obtained in the form of secondary data and hysteresis of published regional financial reports. Findings: Based on the results of the study, it shows that the financial management performance of East Java Province in terms of the level of independence is in the high category (delegative), the effectiveness ratio is very high because its achievements are above the specified target, the activity ratio is not yet balanced between operating expenses and capital expenditures - operating expenses still dominate spending activities, and the growth ratio is still very low. Input for the East Java Provincial Government is to increase or maintain the level of independence and effectiveness of regional finances. Meanwhile, the activity ratio, especially capital expenditures, needs to be increased, and the growth ratio is still very low and has a downward trend during the study period. Paper type: a Research Paper